The Effectiveness of Discharge Planning Implementation on the Quality of Life of Post Opname Patients with Heart Failure at Hospital - Aprin Rusmawati; Alfian Fawzi; Nisa Himmatul Faizah (Universitas STRADA Indonesia, 2024)
Background: Heart failure is a disease with a high rehospitalization rate due to patients not fulfilling recommended therapy, for example, breaking a diet, doing excessive physical activity and lack of understanding during discharge planning. This causes a decrease in the quality of life after patient is discharged. Purpose: This research aims to determine the effectiveness of discharge planning implemention on the quality of life of post-opname patients with heart failure at Bhayangkara Hospital, Kediri City. Method: The type of research used is quantitative research with a descriptive cross-sectional study design. The number of samples in this study were 31 respondents with accidental sampling technique. Results: The results of the non-parametric Spearman rank correlation test analysis obtained a value of p = 0.022 (p <0.05) and a correlation coefficient of 0.411 which is moderate and has a positive direction. This shows that there is a positive relationship between the effectiveness of implementing Discharge Planning on the quality of life of post-hospitalized patients with heart failure at Bhayangkara Hospital, Kediri City. Conclusion: Discharge Planning given to patients with heart failure at Bhayangkara Hospital, Kediri City is not yet effective and needs to be improved. However, the majority of respondents have a good quality of life where respondents experience an increase in socialization, psychology, but still experience physical discomfort.